KIR reconstitution is altered by T cells in the graft and correlates with clinical outcomes after unrelated donor transplantation - Cooley, Sarah (© 2005 by The American Society of Hematology, 2005)
Although unrelated hematopoietic cell transplantation (HCT) is curative for many hematologic malignancies, complications and relapse remain challenging obstacles. Natural killer (NK) cells, which recover quickly after transplantation, produce cytokines and express killer immunoglobulin-like receptors (KIRs) that regulate their cytotoxicity. Some clinical trials based on a KIR ligand mismatch strategy are associated with less relapse and increased survival, but results are mixed. We hypothesized that T cells in the graft may affect NK cell function and KIR expression after unrelated transplantation and that these differences correlate with clinical outcomes. NK cell function was evaluated using 77 paired samples from the National Marrow Donor Program Research Repository. Recipient NK cells at 100 days after both unmanipulated bone marrow (UBM) and T-cell depleted (TCD) transplants were compared with NK cells from their healthy donors. NK cells expressed fewer KIRs and produced more interferon γ (IFN-γ) after UBM compared to TCD transplants. Multivariate models showed that increased NK cell IFN-γ production correlated with more acute graft-versus-host disease (GVHD), and decreased KIR expression correlated with inferior survival. These results support the notion that T cells in the graft affect NK cell reconstitution in vivo. Understanding these mechanisms may result in strategies to improve clinical outcomes from unrelated HCT.